The cat returns [videorecording (DVD)] - Hiiragi, Aoi, 1962- (Walt Disney Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2005)
In an imaginative and lighthearted tale, a young schoolgirl saves the life of a noble cat and is rewarded with a shocking proposal of marriage - to the Cat King's son - and a fateful journey to the extraordinary Kingdom of Cats.